PENGARUH RASIO MOL, SUHU DAN LAMA REAKSI TERHADAP BILANGAN IOD, BILANGAN ASAM, BILANGAN PEROKSIDA DAN KANDUNGAN SULFONAT SURFAKTAN DARI CPO - Hidayati, Sri; -, Illim (Universitas Andalas, 2009)
ABSTRACT A surfactant is a surface-active agent that can be produced by chemical or biochemical synthesis. The main characteristic of a surfactant is having polar and non polar groups at the same molecule (amphiphilic molecules) and forming head-tail configuration. This research as aimed to obtain the optimum condition (reaction temperature, sulphonation reaction and molar ratio) of sulphonation process in producing MES from CPO methyl ester and to investigate the characteristic of MES produced. Measurements conducted include iodine value, acid value, peroxide value and absorbance of Sulfonate. Experimental design used was Response Surface Method (RSM) and Central Composite Design (CCD) with three factors. MES resulted from this best condition had following characteristic or CPO was obtained with ratio of reactants of 1:1.5, reaction time of 4.5 hour and reaction temperature of 108.9ºC with Acid value of 13.32 mg KOH/g sample, Iod value of 41.12 Iod g/100 sample, Peroxide value of 7.6 mmole/1000 g, sulfonat absorbance of 0.76 AU. Keywords : metil ester sulfonat, acid value, iod value, peroxide value